2023
DOI: 10.1177/20503121231177111
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic carpal surgery in carpal tunnel syndrome: A systematic review

Abstract: Objective: Endoscopic carpal tunnel release has become increasingly popular and has shown the advantage of early recovery of hand function with minimal morbidity. In this systematic review, we aimed to summarize the currently available data and describe the reported advantages and disadvantages of endoscopic carpal tunnel surgery for treating carpal tunnel syndrome. Methods: In this study, we followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, which is a set of reporting requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In this nationwide survey in Japan, more than 50 cases were reported in pectus excavatum surgery, carpal tunnel release, craniomaxillofacial tumor excision, facial fracture repair, breast augmentation, and breast reconstruction. Among these, the pectus excavatum and carpal tunnel release procedures are acknowledged as enhancing surgical safety with endoscopic support, and the approaches for these procedures are well established 10,11) . The others are areas where skin scarring should be minimized as much as possible, such as the face and breast, and where the advantages of endoscopic surgery can be exploited.…”
Section: Discussionmentioning
confidence: 99%
“…In this nationwide survey in Japan, more than 50 cases were reported in pectus excavatum surgery, carpal tunnel release, craniomaxillofacial tumor excision, facial fracture repair, breast augmentation, and breast reconstruction. Among these, the pectus excavatum and carpal tunnel release procedures are acknowledged as enhancing surgical safety with endoscopic support, and the approaches for these procedures are well established 10,11) . The others are areas where skin scarring should be minimized as much as possible, such as the face and breast, and where the advantages of endoscopic surgery can be exploited.…”
Section: Discussionmentioning
confidence: 99%
“…As pain is one of the postoperative outcomes, a study conducted by Schroeder et al in 2022 on 1,125 patients with CTS who underwent open and endoscopic surgery found that postoperative opioid use was similar in both groups [ 32 ]. In a study conducted by Liawrungrueang et al in 2022, they found a decrease in short-term pain in the ECTR in a follow-up period extended to two weeks [ 33 ]. Modified ECTR showed a significantly shorter operation time of 33.57 ± 4.21 minutes but no difference in relieving scar pain during the follow-up period [ 29 ].…”
Section: Reviewmentioning
confidence: 99%